SIFAT FISIK DAN MEKANIS PAPAN SEMEN BERBAHAN BAKU BAMBU - . Suhasman; . Bakri (PERENNIAL, 2012)
Fire resistance, termite resistance, and high dimensional stability are among critical attributes of cement board composite as alternative material to replace solid wood products. This study aimed to evaluate characteristics of cement boards made from various age classes of bamboo (1-2 year old, 3-4 year old, and 5-6 year old) and nature of bamboo stem (used and fresh bamboo). Cement board was produced with target density of 0.9 g cm-3, and 30 cm x 30 cm x 1 cm in dimension and the results showed that cement board made from younger bamboo (1-2 year old) had better physical and mechanical characteristics than cement board made from the older bamboo. Most of physical and mechanical characteristics, except for modulus of rupture and dimensional stability, of cement board made from younger bamboo fulfill the Japanese Industrial Standard (JIS) A 5417-2003. The results also showed that cement board made from used bamboo had similar characteristics with cement board made from fresh bamboo. Key words: Young bamboo, used bamboo, cement board